REMEMBERING ACADEMICIAN M.I. PERELMAN - G. V. Ratobylsky (Сеченовский вестник)
The article presents the facts of life and work of the prominent surgeon, professor, academician of RAMS M.I. Perelman. The author traces the life of the scientist, gives his memories of the professional dialogue with M.I. Perelman (consultations, meetings at conferences, etc.).